Peran Perempuan Desa Antap dalam Perekonomian Rumah Tangga Pada Masa Covid-19 - Wiasti, Ni Made; Wedasantara, Ida Bagus Oka (Humanis; Vol 26 No 2 (2022), 2022)
Women in Bali are the group most affected by Covid-19 in the economic sector. They have to think seriously and work hard for the basic daily needs families, as experienced by women in Antap Village, Tabanan Regency, Bali Province. The study aims to reveal the roles and constraints of women in Antap Village on contributing to the household economy sector during the Covid-19 period. The research applies ethnographic methods sourced from interviews with informants by applying health protocols, observations, and literature review that are analyzed and presented descriptively. The article reveals that women in Antap Village have a double burden in maintaining the household economy, especially when the husband experiences layoffs during the Covid-19 period. Meanwhile, women’s constraints in Antap Village to contributing to the household economy are internal and external.